A robust optimization approach for placement of applications in edge computing considering latency uncertainty - Jeong, Jaehee; Premsankar, Gopika; Ghaddar, Bissan; Tarkoma, Sasu (Elsevier, 2024)
Edge computing brings computing and storage resources close to end-users to support new applications and services that require low network latency. It is currently used in a wide range of industries, from industrial automation and augmented reality, to smart cities and connected vehicles, where low latency, data privacy, and real-time processing are critical requirements. The latency of accessing applications in edge computing must be consistently below a threshold of a few tens of milliseconds to maintain an acceptable experience for end-users. However, the latency between users and applications can vary considerably depending on the network load and mode of wireless access. An application provider must be able to guarantee that requests are served in a timely manner by their application instances hosted in the edge despite such latency variations. This article focuses on the placement and traffic allocation problem faced by application providers in determining where to place application instances on edge nodes such that requests are served within a certain deadline. It proposes novel formulations based on robust optimization to provide optimal plans that protect against latency variations in a configurable number of network links. The robust formulations are based on two different types of polyhedral uncertainty sets that offer different levels of protection against variations in latency. Extensive simulations show that our robust models are able to keep the number of chosen edge nodes low while reducing the number of latency violations as compared to a deterministic optimization model that only considers the average latency of network links.
Keywords: 33 Ciencias Tecnológicas::3325 Tecnología de las telecomunicaciones; ODS 9 - Industria, innovación e infraestructura; Telecommunication networks; Uncertainty in network latency; Robust optimization; Edge computing; Application placement